In Situ Transmission Electron Microscopy Investigation of Novel High‐Entropy Silicide (CrFeCoNi)Si Formation at Atomic Scale - Chih‐Lin Chiu; An‐Yuan Hou; Che‐Hung Wang; Chien‐Hua Wang; Jia‐Wei Chen; Chun‐Wei Huang; Shih Hsun Chen; Ying‐Hao Chu; Wen‐Wei Wu (Small Structures)
High‐entropy silicides (HESs) are promising for applications requiring enhanced mechanical properties. Additionally, their unique design concepts make them valuable in microelectronics. However, current research primarily focuses on macroscopic investigations of chemical characteristics and mechanical properties, with limited discussion on synthesis possibilities, atomic‐scale observations, and diffusion dynamics. Herein, a novel HES, (CrFeCoNi)Si, is synthesized on a high‐entropy alloy, Al0.5CrFeCoNi2, via a solid‐state reaction. The silicidation process is examined using high‐resolution transmission electron microscopy (HRTEM) and in situ TEM. Initially, Ni diffuses into the Si substrate, forming Ni2Si at 400 °C. At 500 °C, binary silicides (Ni2Si, FeSi2, and Co2Si) form, while Al oxidizes to Al2O3. At 600 °C, binary silicides transform into ternary silicides (FeNiSi, CoNiSi, and FeCoSi). At 700 °C, Cr forms CrSi2, which reacts with other silicides to produce orthorhombic (CrFeCoNi)Si. The formation mechanism is analyzed via TEM, X‐ray diffraction, and energy‐dispersive X‐ray spectroscopy. Additionally, silicidation trends and diffusion behaviors are recorded using HRTEM. Resistivity measurements reveal that (CrFeCoNi)Si exhibits the lowest resistivity at 700 °C, confirming the cocktail effect. These findings highlight new HESs, dynamic microstructure variations, and low‐resistivity characteristics, providing insights into developing novel high‐entropy ceramic materials.